Degenerative Spine Surgery: Our Experience - Shrestha, Prabin; Singh, Anish M; Dhungana, Isha (Nepal Journal of Neuroscience, 2017)
Degenerative disease is the commonest spinal problem that any neurosurgeon or spinal surgeon encounters in his/her daily practice. Many such cases can be managed conservatively with appropriate investigations, while many others may need surgical intervention. At times it may be diffi cult to make proper decision for the management or for the appropriate surgical intervention. Here we present the retrospective analytical study of our experience in degenerative spinal disease. The main objective of presenting this study is to share our experience. Nepal Journal of Neuroscience, Vol. 14, No. 2, 2017 Page: 25-30